Integrated implementation of Virtual Design and Construction (VDC) and lean project delivery system (LPDS) - Aslam, Mughees; Gao, Zhili; Smith, Gary (Journal of Building Engineering, 2021)
Lean project delivery system (LPDS) has proven to be an effective productivity improvement method. Despite enormous benefits, the construction industry is struggling with effective implementation of LPDS especially in achieving Lean construction (LC) principles like improving the visualization and maintaining effective flow of information. Concurrently, Virtual design and construction (VDC) has opened new windows of opportunities for the construction industry through multidisciplinary integration of design, and construction processes and improving automation through visualization. Using the potentials of VDC to effectively implement LPDS is an area scarcely examined in the current body of knowledge. This study identifies implementation potential of LPDS integrated with VDC, and develops implementation steps to effectively utilize VDC functionalities within the Lean environment using a systematic literature review (SLR) process. The common links between VDC and LDPS are identified through review of academic and practice-based literature. Using a matrix in which potential benefits of VDC are analyzed based on their synergistic impact on Lean principles, a total of 351 positive hypothetical interactions were found between LC and VDC, displaying a strong synergy between them. Moreover, based on the literature, 65 opportunities associated with VDC that support LPDS implementation are identified. Apart from the support by VDC, six (6) areas where Lean intervention can mitigate the challenges faced by VDC are identified. In the end, proposed implementation steps for utilizing VDC within the LPDS environment have been developed. This novel study will help the construction industry improve performance through simultaneous application of LPDS and VDC. •Automate the construction process by using latest technologies like Virtual Design and Construction (VDC).•VDC can support implementation of innovative management philosophies like lean project delivery system (LPDS).•Synergies between VDC and LPDS are explored and presented.•Opportunities provided by VDC in implementing LPDS are identified.•Guidelines for simultaneous application of VDC and LPDS are discussed.